2016
DOI: 10.3389/fbuil.2016.00029
|View full text |Cite
|
Sign up to set email alerts
|

Advanced System Identification for High-Rise Building Using Shear-Bending Model

Abstract: In order to identify physical model parameters of a high-rise building, a new story stiffness identification method is presented based on a shear-bending model and the identification function. Although a shear building model may be the simplest conventional model for representing tall buildings, the system identification (SI) method using that model is not necessarily appropriate. This is because the influence of bending deformation is predominant in such high-rise buildings. For this reason, a shear-bending m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The number of degrees of freedom in this SB model is 2 N, i.e., N for horizontal responses and N for rotational responses. In the previous researches on the SI method using the SB model (Minami et al, 2013;Fujita and Takewaki, 2016), only the horizontal accelerations observed in the numerical/experimental results were used to identify both shear and bending stiffnesses. Since the measurable data are limited in such identification, it is necessary to apply some optimization algorithms to minimize the error in the identification of modal parameters, i.e., natural frequencies.…”
Section: Stiffness Identification Using Subspace Methods and Inverse-mmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of degrees of freedom in this SB model is 2 N, i.e., N for horizontal responses and N for rotational responses. In the previous researches on the SI method using the SB model (Minami et al, 2013;Fujita and Takewaki, 2016), only the horizontal accelerations observed in the numerical/experimental results were used to identify both shear and bending stiffnesses. Since the measurable data are limited in such identification, it is necessary to apply some optimization algorithms to minimize the error in the identification of modal parameters, i.e., natural frequencies.…”
Section: Stiffness Identification Using Subspace Methods and Inverse-mmentioning
confidence: 99%
“…By applying the ARX model to transfer functions, the difficulty in the evaluation of limit value for small SN-ratio data has been overcome (Fujita et al, 2015). On the other hand, the latter problem has been tackled by expanding the SI algorithm to the shear-bending model (SB model) (Fujita et al, 2013;Minami et al, 2013;Fujita and Takewaki, 2016). However, there exists an unstable phenomenon in identifying the bending stiffness due to the low sensitivity of bending stiffnesses on natural frequencies and/or responses.…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of damage detection, this is quite effective. Although the physical parameter technique is preferred in the reliable development of SHM, its research advancement is limited because of the strict requirement on measurements (multiple measurement points) or the necessity of complex manipulation (Hart and Yao, 1977;Udwadia et al, 1978;Shinozuka and Ghanem, 1995;Nakamura, 2000, 2005;Brownjohn, 2003;Nagarajaiah and Basu, 2009;Takewaki et al, 2011;Zhang and Johnson, 2013a,b;Johnson and Wojtkiewicz, 2014;Wojtkiewicz and Johnson, 2014;Fujita and Takewaki, 2016;Song et al, 2017;Takewaki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%